Prognostic significance of increased bone marrow microcirculation in newly diagnosed multiple myeloma: results of a prospective DCE-MRI study - Merz, Maximilian; Moehler, Thomas M.; Ritsch, Judith; Bäuerle, Tobias; Zechmann, Christian M.; Wagner, Barbara; Jauch, Anna; Hose, Dirk; Kunz, Christina; Hielscher, Thomas; Laue, Hendrik; Goldschmidt, Hartmut; et al. (European Radiology, 2015)
Aim of this prospective study was to investigate prognostic significance of increased bone marrow microcirculation as detected by dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) for survival and local complications in patients with multiple myeloma (MM).We performed DCE-MRI of the lumbar spine in 131 patients with newly diagnosed MM and analysed data according to the Brix model to acquire amplitude A and exchange rate constant k ep. In 61 patients a second MRI performed after therapy was evaluated to assess changes in vertebral height and identify vertebral fractures.Correlation analysis revealed significant positive association between beta2-microglobulin as well as immunoparesis with DCE-MRI parameters A and k ep. Additionally, A was negatively correlated with haemoglobin levels and k ep was positively correlated with LDH levels. Higher baseline k ep values were associated with decreased vertebral height in a second MRI (P = 0.007) and A values were associated with new vertebral fractures in the lower lumbar spine (P = 0.03 for L4). Pre-existing lytic bone lesions or remission after therapy had no impact on the occurrence of vertebral fractures. Multivariate analysis revealed that amplitude A is an independent adverse risk factor for overall survival.DCE-MRI is a non-invasive tool with significance for systemic prognosis and vertebral complications.o Qualitative parameters from DCE-MRI are correlated with established factors of disease activity o Increased marrow microcirculation might be a risk factor for loss of vertebral height and fractures o Amplitude A is an independent predictor for shortened overall survival.
EVALuna2:14502